La tarjeta de crédito. Vol. 1 - Núñez Lozano, Pablo Luis (Universidad de Sevilla, 1996)
La Tesis Doctoral tiene por objeto trazar el aspecto de conjunto del fenómeno de la tarjeta de crédito. Tras la delimitación de la figura, realizada a partir de la consideración de sus orígenes y evolución, y luego de tratar del marco jurídico (Derecho Positivo Español, actuaciones de la Comunidad Europea, trabajos de la comisión de las Naciones Unidas para el Derecho Mercantil internacional), se estudian sus caracteres documentales: Idoneidad Legitimadora e Intransmisibilidad. Asimismo se presta atención a las posiciones jurídicas documentalmente representadas por la tarjeta de crédito y a los procedimientos de utilización, distinguiendo entre sus modalidades básicas: las denominadas tarjetas de crédito "bilaterales" y las "trilaterales".
Keywords: Carte de crédit; Credit cards; Tarjetas de crédito

La tarjeta de crédito. Vol. 2 - Núñez Lozano, Pablo Luis (Universidad de Sevilla, 1996)
La Tesis Doctoral tiene por objeto trazar el aspecto de conjunto del fenómeno de la tarjeta de crédito. Tras la delimitación de la figura, realizada a partir de la consideración de sus orígenes y evolución, y luego de tratar del marco jurídico (Derecho Positivo Español, actuaciones de la Comunidad Europea, trabajos de la comisión de las Naciones Unidas para el Derecho Mercantil internacional), se estudian sus caracteres documentales:Idoneidad Legitimadora e Intransmisibilidad. Asimismo se presta atención a las posiciones jurídicas documentalmente representadas por la tarjeta de crédito y a los procedimientos de utilización, distinguiendo entre sus modalidades básicas: las denominadas tarjetas de crédito "bilaterales" y las "trilaterales".
Keywords: Carte de crédit; Credit cards; Tarjetas de crédito

La tarjeta de crédito. Vol. 2 - Núñez Lozano, Pablo Luis (Universidad de Sevilla, 1996)
La Tesis Doctoral tiene por objeto trazar el aspecto de conjunto del fenómeno de la tarjeta de crédito. Tras la delimitación de la figura, realizada a partir de la consideración de sus orígenes y evolución, y luego de tratar del marco jurídico (Derecho Positivo Español, actuaciones de la Comunidad Europea, trabajos de la comisión de las Naciones Unidas para el Derecho Mercantil internacional), se estudian sus caracteres documentales:Idoneidad Legitimadora e Intransmisibilidad. Asimismo se presta atención a las posiciones jurídicas documentalmente representadas por la tarjeta de crédito y a los procedimientos de utilización, distinguiendo entre sus modalidades básicas: las denominadas tarjetas de crédito "bilaterales" y las "trilaterales".
Keywords: Carte de crédit; Credit cards; Tarjetas de crédito

Two essays on political influence and the regulation of financial markets - Eckel, Doug (Virginia Tech, 1996)
I examine two potential instances of rent-seeking in financial markets in the 1980s. In the first essay I test whether managers engage in political activity designed to influence federal regulation of the market for corporate control. In the second, I examine whether firms in the financial services sector attempt to affect bank deregulation. Using Federal Election Commission data, I find campaign contributions by corporate political action committees (PACs) are negatively related to levels of inside ownership, my main proxy for managerial vulnerability to hostile tender offers. Contribution patterns for firms with less than 20% insider ownership are relatively highly correlated, and differ from those of firms with greater than 20% inside ownership. Low inside ownership firms have slightly higher levels of contributions to legislators on particular House and Senate committees proposing relevant legislation. However, when I analyze the impact of contributions on legislator support for regulation I find no statistical support for a theory of vote-buying. I conclude that corporate political behavior is tied to levels of inside ownership, and comprises an alternate index of manager-shareholder conflict. Using a similar approach to analyse the financial services industry, I also find significant patterns in political action committee (PAC) campaign contributions for depository (commercial bank and thrift) and non-depository (brokerage and insurance) sectors of the financial services industry during the 98th Congress (1983-84). Contributions by depository firm PACs appear not only to purchase access to legislators serving on important banking committees crucial to their interests, but are also a significant determinant of votes for repealing sections of the Glass-Steagall Act. Nondepository contributions do not appear to influence votes directly, even though the brokerage and insurance sectors effectively lobbied House Banking Committee chairman Fernand St Germain to enforce the regulatory status quo. When I measure the rents at stake in the legislation using a two-factor market model event study approach, I find that the passage of legislation in the Senate had a positive affect on depository firm returns, implying the sector's lobbying effort was justified. However non-depository PACs lobbied just as extensively, and did not experience significant abnormal returns over the same event period, even though this round of deregulation should have been a zero-sum game between the affected sectors of the industry. I then measure the correlation between the market value impacts of new legislation and contribution amounts for individual firms within the sectors. I find rents are correlated with political activity, even for firms in the non-depository sectors.
Keywords: Corporate control; Financial institutions; Financial markets; Regulation

Les personnes morales de droit public dans les procédures collectives - Droin, Evelyne (Université Paris 9 Dauphine, 1996)
L'intervention des personnes morales de droit public en faveur des entreprises en difficulté, due à la multiplication des procédures collectives, a été légitimée par la mise en place d'un cadre juridique et de conditions d'intervention. C'est une manifestation du droit économique qui appelle la transgression de la frontière entre le droit public et le droit privé. Celle-ci se manifeste notamment, dans la mise en œuvre de la responsabilité des personnes morales de droit public du fait de leurs interventions, par l'examen des divers fondements juridiques de leur responsabilité. D'autre part, les personnes morales de droit public sont parties à la procédure collective en tant que créancières. Elles ont à ce titre une place particulière mais leurs droits ont été modifies et le droit positif révèle un équilibre entre les intérêts publics et les intérêts privés. Par ailleurs, si les personnes morales de droit public ne peuvent être débitrices dans une procédure collective, certaines situations de fait sont analysées qui conduisent à proposer une procédure de redressement financier à leur égard. Enfin, l'interventionnisme économique de l'Etat et des collectivités locales par l'intermédiaire de sociétés de droit privé génère des difficultés d'application du droit des procédures collectives issues de l'imbrication du droit privé et du droit public et même une inapplicabilité de fait.
Keywords: Entreprises en difficulté; Personnes publiques; Économie mixte

Essai de l'assurance en "valeur à neuf" des véhicules terrestres à moteur sur le marché camerounais - Abega Neme, Ignace (Institut International des Assurances (IIA), 1996)

L'amélioration du fonctionnement du système de la carte brune C.E.D.E.A.O. par organisation rationnelle des bureaux nationaux et l'harmonisation des législations des pays membres - Adamaheto Akuete, Kafui (Institut International des Assurances (IIA), 1996)

Contribution à la protection juridique du consommateur dans les pays en voie de développement : Exemple particulier des pays d'Afrique - Adjita, Shamsidine Akrawati (Université Clermont-Ferrand 1, 1996)
Keywords: Afrique; Consommateur (protection); Défense du consommateur

Le marché Togolais de l'assurance-vie : Evolution et perspectives - Akpe Aku, Sama (Institut International des Assurances (IIA), 1996)

Assurance et secteur informel : Cas de l'assureur vie au Niger - Assamadou, Kane (Institut International des Assurances (IIA), 1996)

contribution à la souscription des risques offshore dans les pays de la CIMA - Bantsimba, Brice F. (Institut International des Assurances (IIA), 1996)

Recherche et fidélisation de la clientèle - Bayi, Jean-Marie Vianney (Institut International des Assurances (IIA), 1996)

U.A.B-vie : Recherche et fidélisation de la clientèle - Bayi, Jean-marie Vianney (Institut International des Assurances (IIA), 1996)

Le développement de l'assurance <<vie>> dans un état de la CIMA : Le cas du Cameroun - Bessandje, Laoundoye (Institut International des Assurances (IIA), 1996)

Approche d'élaboration d'une stratégie de développement de la branche assurance de personnes en régime I.A.R.D : Maladie et Individuelle accidents. cas de l'alliance Africaine d'assurances - Bohoui Douzoh, gabriel (Institut International des Assurances (IIA), 1996)

Le risque de change en réassurances : Peut-on s'en prémunir? Le cas de la société africaine de réassurance (Afrique) - Bossou Dossou, Edmond (Institut International des Assurances (IIA), 1996)

Quelques aspects de la problématique de l'assurance des marchandises transportées - Boubacar, Ousmane (Institut International des Assurances (IIA), 1996)

Plan de redressement d'une société en difficulté dans la perspective du code CIMA : Cas des assurances et réassurances du Congo (A.R.C) - Bouka, Jean Claude (Institut International des Assurances (IIA), 1996)

L'assurance << pertes d'exploitation >> des artisans et commerçants - Danfakha, Dembo (Institut International des Assurances (IIA), 1996)

Contribution à l'étude de la comptabilité technique de réassurance - Diouf, Niokhobaye (Institut International des Assurances (IIA), 1996)

La définition d'une stratégie commerciale : le cas de l'A.R.C. - Ebalet, Marien Symphorien (Institut International des Assurances (IIA), 1996)

La maîtrise des effets de l'inflation dans le règlement des sinistrés d'une société d'assurances - Ebela, Venant (Institut International des Assurances (IIA), 1996)

L'assurance et le secteur informel : Comment établir une liaison harmonieuse? - Essam, Alfred (Institut International des Assurances (IIA), 1996)

République Centrafricaine : Nécessité de l'institution d'une assurance mortalité du Bétail - Klabe, Barthélémy (Institut International des Assurances (IIA), 1996)

la marge minimum de solvabilité : Quelle utilité et quelle efficacité face aux risques d'insolvabilité des sociétés d'assurances ? (cas des pays de la CIMA) - Kone, Mamadou (Institut International des Assurances (IIA), 1996)

La délocalisation des placements et ses implications : Le cas dees Etats de la CIMA - Kouakou Bah, Simplice Roger (Institut International des Assurances (IIA), 1996)

La problématique de l'assurance vie en République Centrafricaine - Lembe-Beina, Eric Bertrand (Institut International des Assurances (IIA), 1996)

L'audit d'une compagnie d'assurance dans un Etat "CIMA" - Mba Nze, Alain (Institut International des Assurances (IIA), 1996)

Les critères de solvabilité du code CIMA et la protection économique du consommateur : Une application à l' assurance vie - Mbiegue, Pierre (Institut International des Assurances (IIA), 1996)

L'assurance off shore au Cameroun - Messanga Messanga, Benoit Symplice (Institut International des Assurances (IIA), 1996)

La fusion des sociétés IARD du groupe UAP sur le marché Gabonais : Enjeux et perspectives - Minko M'evouna, Olivier (Institut International des Assurances (IIA), 1996)

L'assurance et le secteur informel au Cameroun - Mvogo, Damien (Institut International des Assurances (IIA), 1996)

L'assurance des véhicules terrestres à moteur : Etude comparative de l'indemnisation des victimes avant et après l'entrée en vigueur du code CIMA - Ndiaye, Alioune Badara (Institut International des Assurances (IIA), 1996)

L'assurance et le financement de l'économie dans les pays de la CIMA : Cas de la république centrafricaine - Ndorman, Daniel (Institut International des Assurances (IIA), 1996)

La disribution des assurances-vie des particuliers dans un pays de la conférence Interafricaine des marchés d'assurances (CIMA) à faible culture d'assurance : Le cas de Gabon-vie - Ngoa Mboulou, Désiré (Institut International des Assurances (IIA), 1996)

Programme d'assainissement du secteur ivoirien des assurances : Evaluation et mesures de redressement - Ouedraogo, Jean-Paul (Institut International des Assurances (IIA), 1996)

L'assurance maritime et transports développement et problèmes : Cas de la C.C.A.R - Siewe Nganjui, Roger François (Institut International des Assurances (IIA), 1996)

De la théorie à la pratique, le technicien des assurances au pieds du mur - Soro, Gninadéma (Institut International des Assurances (IIA), 1996)

Improving the administration of justice through the implementation of third party alternative dispute resolution processes: An analysis of process productivity and disputant strategic behavior - Stanford, John D. (Ohio State University, 1996)
The institutionalization of alternative dispute resolution (ADR) processes is the most recent development in the policy effort to reform the American civil justice system. However, the research is inconclusive and contradictory on the performance of ADR processes in institutionalized settings. This study introduces a production m odel of third party dispute resolution processes to compare the performance of court annexed arbitration, judicial settlem ent conference, and trial processes. To explain the processes’ performance, a strategic behavior model of third party dispute resolution processes identifies four strategic behaviors which influences process perform ance: integrative, distributive, opportunistic, and distributive. Through conceptualization of the m odels, several hypotheses are developed. This study introduces a production m odel of third party dispute resolution processes to compare the performance of court annexed arbitration, judicial settlem ent conference, and trial processes. To explain the processes’ performance, a strategic behavior model of third party dispute resolution processes identifies four strategic behaviors which influences process perform ance: integrative, distributive, opportunistic, and distributive. Through conceptualization of the m odels, several hypotheses are developed. This study concludes that the court annexed arbitration is the best performing process. Of the various dispute, disputant, and process characteristics identified to explain process perform ance, only the disputant’s perception of process equity during the process is significant and positive. The policy inference is that policy makers can reduce disputant costs while improving delay, process equity, and satisfaction through court-annexed arbitration.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitraje; Arbitration; Mediation; Third party

Adaptation de l'assurance vie au code CIMA - Tamo, Blaise Emmanuel Dzudie (Institut International des Assurances (IIA), 1996)

La fraude à l'assurance dans les Etats de la CIMA : Cas du Cameroun - Toyum, Pierre (Institut International des Assurances (IIA), 1996)

L'indemnisation des prejudices corporels dans le code CIMA. : Incidence sur le role du juge - Yahaya Mahaman, Nasser (Institut International des Assurances (IIA), 1996)